2004
DOI: 10.1016/j.ydbio.2003.09.019
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF directs stromal cell polyploidy and decidualization via cyclin D3 during implantation

Abstract: Stromal cell polyploidy is a unique phenomenon that occurs during uterine decidualization following embryo implantation, although the developmental mechanism still remains elusive. The general consensus is that the aberrant expression and altered functional activity of cell cycle regulatory molecules at two particular checkpoints G1 to S and G2 to M in the cell cycle play an important role in the development of cellular polyploidy. Despite the compelling evidence of intrinsic cell cycle alteration, it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 50 publications
4
120
0
Order By: Relevance
“…Since HB-EGF has been shown to be regulated by progesterone during decidualization and tightly related to the polyploidization of decidual cells, 25,26 we assumed that HB-EGF may be involved in mediating the regulation of E2F8 expression in mouse uterus during decidualization. Compared with control group, the stromal cells treated with HB-EGF showed an increased proportion of tetraploid (Fig.…”
Section: Hb-egf/egfr/erk/stat3 Signal Pathway Regulates E2f8 Expressimentioning
confidence: 99%
“…Since HB-EGF has been shown to be regulated by progesterone during decidualization and tightly related to the polyploidization of decidual cells, 25,26 we assumed that HB-EGF may be involved in mediating the regulation of E2F8 expression in mouse uterus during decidualization. Compared with control group, the stromal cells treated with HB-EGF showed an increased proportion of tetraploid (Fig.…”
Section: Hb-egf/egfr/erk/stat3 Signal Pathway Regulates E2f8 Expressimentioning
confidence: 99%
“…Previous studies in rodents have shown that the route of administration is a major determinant for the transfection efficiency in somatic tissues by adenoviral recombinants (Huard et al, 1995). However, limited information is currently available for in vivo adenoviral gene delivery in the uterus (Tan et al, 2004). To explore the potential route for ADV-Cre delivery into uterine cells during early pregnancy, we first examined whether a direct infusion of the virus into the uterine lumen is suitable for conditionally targeting uterine cells.…”
Section: Intraluminal Adenoviral Cre Infusion Induces Conditional Genmentioning
confidence: 99%
“…Generation of the replication-defective adenoviral vector for bacteriophage P1 Cre gene (ADV-Cre) followed the technique described by us (Tan et al, 2004). In brief, a 1.2-kb fragment (Xba1/SmaI) of a Cre gene containing the N-terminal nuclear localization signal (NLS) was derived from an expression clone, pBS/RIP-Cre-GH (generously provided by Holger Kulessa and originally developed by Christopher Wright, Vanderbilt University) and subsequently subcloned into XbaI/ECoRV sites of the shuttle vector, pAdTrack-CMV.…”
Section: Construction Of Recombinant Adenoviral Vectors For Cre Genementioning
confidence: 99%
See 2 more Smart Citations